Footsteps on the sacred earth : Southwestern Collection of the Bata Shoe Museum - Oakes, Jill E. 1952-; Riewe, Roderick R., 1942- (printed for The Bata Shoe Museum by University of Toronto Press, 1999)
"Material and spiritual cultures of the indigenous peoples of the Southwest: Anasazi, Pueblo, Navajo, Apache, Kiowa and Comanche"--Resumé vydavatele